Body-mapping based on thermographic measurements under different influencing factors - Salopek Čubrić, Ivana (Array, 2021)
The presented research focuses on the use of thermography to observe influences of different influencing factors on the changes of lower body temperatures. Based on the outcomes of the research fit of garment plays an important role for the retention of heat between the textile material and skin, especially in the zone of both upper and lower shin. Also only tight model of trousers is capable to preserve the temperature in zones of thigh and knees of male volunteer. The given body-maps present differences in values of average temperatures (ΔT) considering the garment fit. In the indoor environment, tight model of female trousers has significant influence on the average temperature in the zone of upper shin. This observation is even more pronounced in the outdoor environment. For the male volunteer, higher differences, between temperatures are seen in the outdoor environment only.